TEOLOGI EKUMENIS SEBAGAI WUJUD KASIH KRISTUS DALAM KEHIDUPAN OIKUMENIS - Riski, Riski; Sjahthi, Herman; Darmaka, Benediktus James Widya (RERUM: Journal of Biblical Practice, 2025)
Ecumenical theology is a reflection of faith that affirms Christ's love as the foundation of church unity and ecumenicallife. Christ's love is understood as a unifying force that transcends differences in denomination, doctrine, or tradition, so that diversity is no longer seen as a barrier but as a richness of faith that enriches the body of Christ. Within this framework, ecumenism is not an attempt to erase the church's identity, but rather an effort to affirm the core of the Gospel, which is centered on God's unifying love. Through literature reviews, theologians emphasize the importance of dialogue and collaboration based on openness and honesty. Ecumenical dialogue does not simply bring together differing perspectives, but rather serves as a means of mutually enriching our understanding of faith and broadening our perspectives on God's work. Christ's love serves as a bridge that transcends historical and cultural barriers, enabling the church to see diversity as part of God's plan. Ecumenical life is understood as a call to present God's inclusive, transformative, and practical love. Inclusive love embraces differences, transformative love brings change toward justice and peace, and practical love is embodied in shared service. Thus, ecumenical theology does not stop at discourse, but becomes a concrete practice of Christ's love, proclaiming God's peace to the world.  Teologi ekumenis merupakan refleksi iman yang menegaskan kasih Kristus sebagai dasar persatuan gereja dan kehidupan oikumenis. Kasih Kristus dipahami sebagai kekuatan pemersatu yang melampaui perbedaan denominasi, doktrin, maupun tradisi, sehingga keberagaman tidak lagi dipandang sebagai penghalang, melainkan sebagai kekayaan iman yang memperkaya tubuh Kristus. Dalam kerangka ini, ekumenisme bukanlah upaya menghapus identitas gereja, melainkan usaha untuk menegaskan inti Injil yang berpusat pada kasih Allah yang menyatukan. Melalui kajian literatur, para teolog menekankan pentingnya dialog dan kerja sama yang dilandasi keterbukaan dan kejujuran. Dialog oikumenis tidak sekadar mempertemukan pandangan yang berbeda, melainkan menjadi sarana saling memperkaya pemahaman iman dan memperluas perspektif tentang karya Allah. Kasih Kristus menjadi jembatan yang mampu menembus sekat historis maupun kultural, sehingga gereja dapat melihat keberagaman sebagai bagian dari rencana Allah. Kehidupan oikumenis dipahami sebagai panggilan untuk menghadirkan kasih Allah yang inklusif, transformatif, dan praksis. Kasih yang inklusif menerima perbedaan, kasih yang transformatif membawa perubahan menuju keadilan dan perdamaian, dan kasih yang praksis diwujudkan dalam pelayanan bersama. Dengan demikian, teologi ekumenis tidak berhenti pada wacana, melainkan menjadi praksis nyata kasih Kristus yang menyatakan damai sejahtera Allah bagi dunia.